Pengaruh Tingkat Penggunaan Isi Rumen Sapi Terfermentasi dalam Ransum Terhadap Penampilan Itik Fase Starter - Manginte, Nelson; Rumetor, SientJe D.; Rahardjo , Dwi D. (Jurnal Ilmu Peternakan dan Veteriner Tropis (Journal of Tropical Animal and Veterinary Science), 2006)
The object of this experiment was to know the effect of rumen content on duck performance at starter period. Randomized Completely Design consisted of 5 treatments and 4 replications was used in this experiment. Each experiment unit consisted of 2 ducks at starter period, thus tottaly was 40 ducks. Four dietary treatments comprised 1) basal diet without rumen content; 2) basal diet supplemented v.ith 5% of rumen content; 3) basaJ diet supplemented v.ith 10% of rumen content; 4) basal diet supplemented with 15% ofrumen content; 5) basal diet supplemented with 20% of rumen content. Variable determine in this experiment were feed intake, body gain, and feed efficiency. In general, use of cow's rumen content in diet increased feed intake, body gain, and feed efficiency. Supplementation of rumen content at level of 10% in diet had the best result in this experiment.